Effectiveness of the percentage of contribution of some variables Bayocnameteki performance skill to hit the ball crushing back plane - Ali, Taraq (Journal of Physical Education, 2011)
Came the importance of research to identify the effectiveness of the contribution of some variables Albiocnamatkip performance skill spike back. Due to the lack of information mechanical skill spike, the effectiveness of its contribution to pay a researcher to study this subject to find out the effectiveness and the different contribution of variables Albaiocnamatkip stages of performance skills. So the goal of research to identify the stages of the spike back and its relationship to variables Albaiocnamatkip and the contribution of these variables stages spike the ball back plane And imposes the researcher that there is a statistically significant relationship between variables Albaiukinmatkip and performance skills of the landslide hit the ball back the plane and also that there is variation in the effectiveness of the contribution rate to the variables Albiukinmetekih stages and four in the back of the spike volleyball . The researcher used the descriptive style of relations and relational research sample included players club volleyball and Industry’s (8) players and the researcher to many of the conclusions was delusional Reached its highest percentage of contribution of the variables Albiukinmatikp in the skill of spike back in the speed of approach, followed by the angle of departure and after Srapalantlaq then angle bracket trunk and speed of oceanic and researcher recommends interest grounds mechanical stages of the performance of the third (getting close, upgrade, hitting the ball) by trainers and teachers during the training modules to enhance the level of offensive skills in the game that includes commentary, presentation, and some pictures and movies illustrations of the skills required